Digitalisasi Logo dan Pelatihan Penggunaan Media Sosial Bisnis Pada UMKM Eka Multi Teknik - Made Liandana; Gede Angga Pradipta; Putu Desiana Wulaning Ayu; I Gusti Ngurah Putu Arya Wijaya; Aditya Naray Artamerta; I Kadek Agus Ari Setiawan (Jurnal Pengabdian Literasi Digital Indonesia, 2023)
Business recognition through social media is very important in the midst of the ever-increasing development of internet users. Through social media, business profiles can be known by users, the more recognized the potential to increase the number of customers will be more open. Eka Multi Teknik is an UMKM engaged in repairing air conditioners, refrigerators, washing machines and other devices. In particular, these UMKM have not introduced their business through digital platforms, besides that the identity logo business is not yet available in digital form, making it difficult to apply it on social media and other digital media. So the solution offered is to make an identity logo in digital form, Instagram social media, and training on using Instagram social media for business. From the results of this activity, the partners were very enthusiastic about participating in the activity, this can be seen from: the participation of partners in providing a place and time for activities, as well as discussions and questions and answers conducted by partners with the service team. Partners have also been able to use Instagram social media for business, this can be seen from the results of content posts that have been made by partners, including how to use Instagram's Insights feature for business